2011
DOI: 10.1007/s11240-011-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of antitumour naphthoquinones in transgenic hairy root lines of Lithospermum canescens

Abstract: The effects of medium exchange and methyl jasmonate addition on growth and production of shikonin and its derivatives acetylshikonin and isobutyrylshikonin in hairy root cultures of Lithospermum canescens were investigated. Responses varied depending on the transgenic line and stage of growth at which these lines were subjected to treatment. Shikonin itself was not detected, irrespective of the transgenic line and culture treatment used. A eightfold increase in acetylshikonin and isobutyrylshikonin accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 31 publications
3
6
0
1
Order By: Relevance
“…This high cytotoxic activity in HRs may be due to the higher amount of polyphenolic compounds. Our results agreed with various earlier studies which demonstrated that the HRs displayed higher cytotoxic activities compared to the NTR extracts [39,50,53].…”
Section: Resultssupporting
confidence: 93%
“…This high cytotoxic activity in HRs may be due to the higher amount of polyphenolic compounds. Our results agreed with various earlier studies which demonstrated that the HRs displayed higher cytotoxic activities compared to the NTR extracts [39,50,53].…”
Section: Resultssupporting
confidence: 93%
“…This high cytotoxic activity in hairy roots may be due to the high flavonoid and phenolic content. Our results agreed with various earlier studies which demonstrated that the transgenic roots showed higher antibacterial and cytotoxic activities compared to the nontransgenic roots [ 28 , 29 ]. In conclusion, the present study suggests that transgenic hairy roots of Lactuca serriola could be efficiently used for the antioxidant and medicinal treatments.…”
Section: Resultssupporting
confidence: 93%
“…Besides our experiment, an inverse relationship between biomass and sucrose level was observed by Sykłowska-Baranek et al [59]. However, our results indicate that this correlation is weaker than that between biomass increase and conductivity decrease.…”
Section: Discussionsupporting
confidence: 72%